Thiotepa, busulfan, and cyclophosphamide: A new preparative regimen for autologous marrow or blood stem cell transplantation in high-risk multiple myeloma - Dimopoulos, M.A.; Alexanian, R.; Przepiorka, D.; Hester, J.; Andersson, B.; Giralt, S.; Mehra, R.; Van Besien, K.; Delasalle, K.B.; Reading, C.; Deisseroth, A.B.; Champlin, R.E. (Blood, 1993)
Forty patients with multiple myeloma received thiotepa (750 mg/m2), busulfan (10 mg/kg), and cyclophosphamide (120 mg/kg) (TBC) followed by autologous bone marrow or blood stem cell support. Granulocyte-Colony stimulating factor (G-CSF) was administered to accelerate hematopoietic recovery. Sixty-five percent of all patients responded to this treatment. Eighty-eight percent of patients transplanted in partial remission had a further reduction of the myeloma and 53% achieved a complete remission. Forty-eight percent of patients with refractory myeloma responded. All responding patients transplanted during partial remission or with primary refractory myeloma remain free of progression for a period of 4 to 24 months posttransplant, but the remission duration of patients treated in refractory relapse was short (4 months). Five of 24 patients transplanted with marrow and none of 16 receiving blood stem cells died of treatment-related complications. Use of blood stem cells resulted in more rapid granulocyte and platelet recovery. We conclude that TBC is an effective, relatively well tolerated, preparative regimen for patients with multiple myeloma. © 1993 by The American Society of Hematology.